2010
DOI: 10.1002/bit.22790
|View full text |Cite
|
Sign up to set email alerts
|

Rapid whole monoclonal antibody analysis by mass spectrometry: An Ultra scale‐down study of the effect of harvesting by centrifugation on the post‐translational modification profile

Abstract: With the trend towards the generation and production of increasing numbers of complex biopharmaceutical (protein based) products, there is an increased need and requirement to characterize both the product and production process in terms of robustness and reproducibility. This is of particular importance for products from mammalian cell culture which have large molecular structures and more often than not complex post-translational modifications (PTMs) that can impact the efficacy, stability and ultimately the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 64 publications
7
27
0
Order By: Relevance
“…The product quality was steady state over the time of operation. The steady state product quality that results from lower residence time can be a marked advantage over batch processes where product stability over culture days can be a significant issue (Joshi et al, 2014;Mohan et al, 1993;Pacis et al, 2011;Reid et al, 2010;Robinson et al, 1994). The consistent product quality over ∼30 days also indicates the feasibility of using CHO/DHFR cell line for prolonged duration continuous/perfusion cell culture processes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The product quality was steady state over the time of operation. The steady state product quality that results from lower residence time can be a marked advantage over batch processes where product stability over culture days can be a significant issue (Joshi et al, 2014;Mohan et al, 1993;Pacis et al, 2011;Reid et al, 2010;Robinson et al, 1994). The consistent product quality over ∼30 days also indicates the feasibility of using CHO/DHFR cell line for prolonged duration continuous/perfusion cell culture processes.…”
Section: Discussionmentioning
confidence: 93%
“…Inherently, however, the dynamic nature of the Biologics process results in variable product quality as a function of culture days in both perfusion and batch cell culture processes (Pacis et al, 2011;Reid et al, 2010;Robinson et al, 1994). Mohan et al have specifically shown degradation effects of protease being minimized in continuousflow cultures as opposed to batch processes (Mohan et al, 1993).…”
Section: Introductionmentioning
confidence: 97%
“…Liquid chromatography (LC) at-line with MSD-TOF MS has been used to perform intact antibody analysis for an ultrascale down study, which has been undertaken to investigate a potential impact of downstream processing on the molecular structure of a monoclonal antibody (mAb) and to demonstrate how process operating conditions can impact other unit operations [22]. LC/MSD-TOF analysis allowed for simultaneous detection of the changes that occur to the cleavage of heavy chain C-terminal lysine residues and the glycosylation pattern, as well as the presence of heavy chain/light chain dimers depending on the time of harvest.…”
Section: Applications Of Ms For Biopharmaceutical Process Monitoring mentioning
confidence: 99%
“…Although LC-MS method with SIM detection certainly permits monitoring and quantitation of major glycoforms in cell culture supernatant; however, it is much more challenging to monitor and quantify lower abundant species, which could contain important information, for example, on fucosylation levels and addition of potentially immunogenic sugars, among others. A more recent publication addresses the deficiencies of both the SIM method [23] and the off-line protein A purification approach [22], by utilizing (LC/electrospray quadrupole time-of-flight-MS (LC/ESI-qTOF-MS) system, coupled with an on-line column-switching system equipped with two columns, a protein A affinity column and a reversed-phase (RP) desalting column [24]. Two column-switching systems have been introduced, one targeting intact mAbs, and the other targeting the light and heavy chains of the mAbs.…”
Section: Key Termmentioning
confidence: 99%
“…are minimized. Potential quality issues with stable molecules are addressed as well (Pacis, 2011;Robinson, 1994;Reid, 2010), as continuous processes may be operated with robust control, improving product quality and minimizing heterogeneity.…”
Section: Qualitymentioning
confidence: 99%